Late Neogene Mountain Building of Eastern Kunlun Orogen： Constrained by DEM Analysis - 王岸 王国灿 张克信 向树元 李德威 刘德民 (Journal of earth science (Wuhan, China), 2009)
Topography, as a net result of the dynamic interaction between endogenesis and exogenesis, holds immense information on tectonic uplift, surface erosion and thus mountain building. The eastern Kunlun （昆仑） orogen, which experienced significant Late Neogene tectonic uplift and is located in an arid environment, is advantageous for morphotectonic analysis based on well-preserved tectonic landforms. The digital elevation model （DEM） analysis was carried out for the central segment of the eastern Kunlun orogen based on shuttle radar topography mission （SRTM） data. River longitudinal profile analysis indicates that major rivers across the orogen are characterized by high river gradient indexes and intensive tectonic uplift. Differential uplift was also identified in swath-topography analysis in the studied area, which can be divided into three major tectonic-geomorphie units by orogenicstrike-parallel faults. It is indicated that the most active region is located to the south of the Xidatan （西大滩） fault with significant differential uplift. Another identified fault with differential uplift is the Middle Kunlun fault; however, the timing of which is suggested to be much older than that of the Xidatan fault. These analyses are concordantly supported by both field survey and studies of thermochronology, which in turn indicates that the DEM analysis bears great potential in morphotectonic analysis.